2012
DOI: 10.1016/j.bioelechem.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

In situ regeneration of NADH via lipoamide dehydrogenase-catalyzed electron transfer reaction evidenced by spectroelectrochemistry

Abstract: NAD/NADH is a coenzyme found in all living cells, carrying electrons from one reaction to another. We report on characterizations of in situ regeneration of NADH via lipoamide dehydrogenase (LD)-catalyzed electron transfer reaction to regenerate NADH using UV-vis spectroelectrochemistry. The Michaelis-Menten constant (Km) and maximum velocity (Vmax) of NADH regeneration were measured as 0.80 ± 0.15 mM and 1.91 ± 0.09 μM s-1 in a 1-mm thin-layer spectroelectrochemical cell using gold gauze as the working electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The UV-Vis spectra of the EPS at various potentials were measured using spectroelectrochemical analysis, which was performed using a thin-layer spectroelectrochemical cell with a Pt gauze working electrode, an Ag/AgCl reference electrode, and a Pt wire counter electrode36. The optical length of the spectroelectrochemical cell was 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The UV-Vis spectra of the EPS at various potentials were measured using spectroelectrochemical analysis, which was performed using a thin-layer spectroelectrochemical cell with a Pt gauze working electrode, an Ag/AgCl reference electrode, and a Pt wire counter electrode36. The optical length of the spectroelectrochemical cell was 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The regeneration typically takes place in a three‐reaction sequence (Figure 16), as was shown in the work of Chen et al., where synthesis of lactate from pyruvate was achieved in a membrane packed‐bed reactor [170] . Another instance of methyl viologen mediated electroreduction of NAD + with lipoamide dehydrogenase (LDH), also known as diaphorase, occurs at low cathodic overpotential [171] . In‐situ spectrophotometric study showed that the amount of NADH produced was incumbent on the LDH concentration while the rate of NADH regeneration depended on initial NAD + concentration and followed Michaelis–Menten kinetics.…”
Section: Electrochemical Regeneration Methodsmentioning
confidence: 93%
“…Similar to NAD(P) + reduction, direct electrochemical oxidation of NAD(P)H on a bare electrode also takes place at a high overpotential [17–178] . Cyclic voltammograms fro...…”
Section: Electrochemical Regeneration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Puesto que hasta hace poco no existía ningún dispositivo comercial para realizar medidas espectroelectroquímicas, han sido muchos los grupos que han utilizado este tipo de técnica multirrespuesta desarrollando sus propias celdas y dispositivos de medida. Las técnicas más utilizadas y para las que más desarrollos instrumentales de medida se han propuesto son la espectroelectroquímica [186][187][188] , las películas finas de oro 189,190 o las mallas metálicas de oro [191][192][193]…”
Section: Rayos X 166unclassified